The Development of Literacy Culture to Improve Students’ Understanding of Islamic Religion Subject - Khozin Khozin; Zakiyatus Saidah; Abdul Haris (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to describe the efforts to develop a literacy culture in SMA Negeri 1 Batu in enhancing students' understanding of PAI learning materials, as well as the benefits gained by students with the existence of a school litersai culture. This research method uses a qualitative approach to the type of case study research. Data collection techniques using observation, in-depth interviews and documentation. The results of the study show: (1) the implementation of the literacy culture development program at SMA Negeri 1 Batu is largely in accordance with the design of the government's main about GLS. By implementing mandatory reading activities for 10 minutes before learning, the availability of literacy corner facilities in every corner of the classroom, as well as adequate libraries as the main source of literacy in schools. (2) there are many benefits obtained by students with the existence of literacy activities in schools in improving their understanding, especially on PAI subjects